Examining leadership practices among public servant in Klang Valley - Muhammad Rasihan, Arif (2021)
This research examines examining leadership practices among public servant in Klang Valley, and highlight on the relationship of three important variables that are guidance, strategic thinking and communication with engagement in leadership. This research data revealed a pattern of agreement between leaders and those being led with good leadership practices in the government sector. Respondents of this research were among civil servants of Implementing Group Management Leadership (Executive Officer) and subordinate personnel employed in the National Registration Department (JPN) at the Urban Transformation Center (UTC) across the Klang Valley. The Blue Ocean Leadership (BOL) was reffered as the most relevant model to this research framework, where the results show guidance, strategic thinking and communication have significant relationship with engagement in leadership among the public servants. This academic analysis would give some guidelines for all leaders, not only for the public sector but private sectors in both technically and theoretically. Leaders should learn the importance of formulating, planning, organizing, and executing effective policies and activities in their leadership practices through proper guidance, strategic thinking and communication.